Implementation of Improved Finite Elements Over Circular Cross-Section Subjected to Effect of Non-Uniform Wind - Bekiroglu, Serkan; Ayvaz, Yusuf (TURKISH CHAMBER CIVIL ENGINEERS, 2015)
In this study, a finite element program based on p-version finite element method (pFEM) and augmented by blending function method is coded. The program has a solid 3 dimensional finite element defined in cartesian coordinates, by which application of continuous or discontinuous nonlinear loads are taken into account and exact representation of curved edge and/or surface boundary is performed. With the aid of the coded program, a series of static analyses under defined wind loads for uniform and non-uniform loadings according to TS 498 and non-uniform loading according to pr EN 1991-1-4 are carried out on an industrial chimney with a circular cross-section. It is concluded that the coded program gives reliable results. Due to the capability of modeling of non-uniform loadings it is observed that the standards may lead to vastly different results.
Keywords: p-version finite element method (pFEM); finite elements; blending function method; finite element having curved surfaces; non-uniform loading; wind loading; H-P VERSIONS; INTERPOLATION; EFFICIENCY; MECHANICS; Engineering